Fungal Communities of the Pine Wilt Disease Complex: Studying the Interaction of Ophiostomatales With Bursaphelenchus xylophilus - Vicente, Cláudia S. L.; Soares, Miguel; Faria, Jorge M. S.; Espada, Margarida; Mota, Manuel; Nóbrega, Filomena; Ramos, Ana P.; Inácio, Maria L. (Frontiers in Plant Science, 2022)
Considered one of the most devastating plant-parasitic nematodes worldwide, Bursaphelenchus xylophilus (commonly known as pinewood nematode, PWN) is the causal agent of the Pine Wilt Disease in the Eurasian coniferous forests. This migratory parasitic nematode is carried by an insect-vector (Monochamus spp.) into the host tree (Pinus species), where it can feed on parenchymal cells and reproduce massively, resulting in the tree wilting. In declining trees, PWN populations are strongly dependent on fungal communities colonizing the host (predominantly ophiostomatoid fungi known to cause sapwood blue-staining, the blue-stain fungi) which not only influence their development and life cycle but also the number of individuals carried by the insect-vector into a new host. Our main aim is to understand if PWN-associated mycobiota plays a key-role in the development of PWD, in interaction with the PWN and the insect-vector, and into which extend can be targeted to disrupt the disease cycle. For this purpose, we characterized the fungal communities of Pinus pinaster trees infected and non-infected with PWN in three collection sites in Continental Portugal with different PWD temporal incidences. Our results showed that in non-infected P. pinaster mycoflora is more diverse (in terms of abundance and fungal richness) than PWN-infected pine trees in the most recent PWD foci, as opposed to the fungal communities of long-term PWD history sites. Then, due to their ecological importance for PWN survival, representatives of the main ophiostomatoid fungi isolated (Ophiostoma, Leptographium, and Graphilbum sp.) were characterized for their adaptative response to temperature, pairwise competition in-between taxa, and as food source for PWN. Under the conditions studied, Leptographium isolates showed promising results for PWN control. They could outcompete the other species, especially O. ips, and significantly reduce the development of PWN populations when compared to Botrytis cinerea (routinely used for PWN lab culturing), suggesting thus to be a natural antagonist not only for the other blue-stain species but also for the PWN.